Universalization of Democratic Constitutionalism and The Work of Constitutional Courts Today - Asshiddiqie, Jimly (Constitutional Review, 2015)
Modern constitutions with its content of values and legal norms and universal ethics contained therein continuously inôªuence the paradigm of thought and the system of practice and constitutional democratic political regimes in the world. We may say that nowadays we are in the midst of the current development of new thoughts in the study of constitution and the practice of constitutional judiciary in the world, namely the phenomenon of âuniversal democratic constitutionalism.â Indonesia and all the states are experiencing the development of the same inôªuence, so that way of worôing of the Constitutional Court as an institution to safeguard democracy and being the upholder of the constitution shall also catch the moral signs and messages behind that new development with a critical stance, so that each of its decisions can truly produce justice, certainty, and is solvent in nature vis-Ã -vis the constitutional problems occurring in the public of the respective states.